The Journal Krítica: Between “Renewal” and “Popular Democracy”, 1978-1991 - Dinamarca Opazo, Renato Andrés (Revista de Historia Social y de las Mentalidades, 2023)
We analize a journal of an intellectual generation that sought to renew Chi- lean socialism from the political role it assigned to autonomous social movements, dis- puting the popular character that democracy should have. In this sense, they strained the process of reinventing the concept of democracy from a political position related to their membership in parties of the left linked to christianity and with a commitment to what they called a “popular alternative” for Chile. Thus, in different periods they sought to elaborate democratization proposals from a perspective that prioritized the process of rebuilding the popular movement, a political subject that, for them, represented the possibility of building a radical democracy in Chile.
Keywords: Intellectual Generation; Political Journal; Renewal Socialism; Popular Democracy